Tiryāq in traditional Persian medicine: a survey of antidotal plants and their modern pharmacological potential - Mirhosseini, Haniye; Dadmehr, Majid; Yousefsani, Bahareh Sadat; Seif, Farhad; Eghbalian, Fatemeh (Frontiers in Pharmacology, 2025)
PurposeTiryāq (Theriac) refers to a single or compound medication historically utilized as a general antidote against numerous poisons in several ethnomedical traditions, especially in traditional Persian medicine (PM). This study aims to summarize the traditional uses, phytochemistry, and pharmacological activities of medicinal plants with tiryāq properties, with a particular focus on their anti-hepatotoxic, hepatoprotective, neuroprotective, and cardioprotective activities.MethodsClassical texts of traditional PM were broadly reviewed to extract information about tiryāq and its mechanisms. In addition, a detailed search of scientific databases was performed to validate the pharmacological properties of plants traditionally recognized for their antidotal effects.ResultsThirty-one medicinal plants with antidote properties were identified. The primary function of tiryāq, as described in PM, is to neutralize toxins and bolster the immune system. These plants have cardiotonic, hepatoprotective, and neuroprotective properties. In addition to their antidotal applications, tiryāq remedies were traditionally used to manage chronic cough, stomachache, asthma, colic, and other ailments. Modern pharmacological studies support these applications, highlighting the plants’ antiviral, immunomodulatory, and antioxidant properties, especially against acute respiratory viral infections and other inflammatory circumstances.ConclusionTiryāq plays a pivotal role in fortifying essential organs, including the heart, brain, and liver. Its prophylactic use during epidemics, along with its antioxidant and immune-stimulating properties, underscores its therapeutic potential. Further research is needed to conclusively determine the efficacy and broader therapeutic applications of medicinal plants with tiryāq properties.